DMR50 – the first digital terrain model of Slovakia in the GCCA SR sector - Matej Klobušiak; Miloslav Ofúkaný (Acta Montanistica Slovaca, 2005)
The digital terrain model (DTM) is a complex object of the Primary Database for The Geographic Information System (PD GIS). PD GIS is a component of the Automated Information System of Geodesy, Cartography and Cadastre. The EC initiative INSPIRE defines DTM as one basic element of the National Spatial Data Infrastructure (NSDI). The creation of NSDI is a task of the Action Plan of the Strategy of the Slovak Information Society. The range of the DTM vertical accuracy is described through the metadata. The metadata describes a product in a complex way. The GCCA SR will offer metadata and the solo product of DTM through its organization, the Geodetic and Cartographic Institute in Bratislava (GCI), via the Internet. For this purpose the GCI meaningfuly build a webmap service, GCCA SR Geoportal, which is nearly related with the NSDI concept as well as with the projects of the Eurogeographics association. The paper describes the creation of DMR50, DTM of Slovakia, with the 50x50 meter grid. DMR50 was created by the data processing of the contour lines model from the Basic Map of the Slovak Republic 1:50 000. The testing of the DMR50 vertical accuracy was carried out by the set of geodetic points from the State Levelling Network. DMR50 is a suitable contribution of Slovakia to the creation of the EuroGeographics or INSPIRE–coordinated pan-European products.